Development of computer program to optimize an air conditioning system for local utilization - Frank Murphy anak, Junaidi Kutoi (University Malaysia Sarawak, UNIMAS., 2004)
This project is regarding the development of a computer program in which it aims to optimize the air conditioning system in the local area. Before the development process of the program, various conditions that can influence the optimizing process of the air conditioning system must be identified. These review includes the problems' background, calculate the heat gain and to optimize the energy usage.